2001
DOI: 10.1074/jbc.m104769200
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Response Element-binding Protein Content Is a Molecular Determinant of Smooth Muscle Cell Proliferation and Migration

Abstract: We hypothesized that cAMP response element-binding protein (CREB) could function as a molecular determinant of smooth muscle cell fate. In arterial sections from the systemic and pulmonary circulation, CREB content was high in proliferation-resistant medial subpopulations of smooth muscle cells and low in proliferation-prone regions. In vessels from neonatal calves exposed to chronic hypoxia, CREB content was depleted and smooth muscle cell (SMC) proliferation was accelerated. Induction of quiescence by serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
136
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(145 citation statements)
references
References 36 publications
9
136
0
Order By: Relevance
“…In addition, by using ChIP assays we provide the first evidence for a direct binding of Ser-133-phosphorylated CREB to the consensus sites within the endogenous NOR1 promoter. CREB Ser-133 phosphorylation has been demonstrated to be induced by PDGF in SMC (54), and PDGF-induced CREB phosphorylation is mediated through ERK-MAPK signaling (55). Additionally, recent in vivo studies by Tokunou et al (56) observed that proliferating neointimal SMC express high levels of phosphorylated CREB, thereby providing the basis for induced NOR1 expression during neointimal SMC proliferation.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, by using ChIP assays we provide the first evidence for a direct binding of Ser-133-phosphorylated CREB to the consensus sites within the endogenous NOR1 promoter. CREB Ser-133 phosphorylation has been demonstrated to be induced by PDGF in SMC (54), and PDGF-induced CREB phosphorylation is mediated through ERK-MAPK signaling (55). Additionally, recent in vivo studies by Tokunou et al (56) observed that proliferating neointimal SMC express high levels of phosphorylated CREB, thereby providing the basis for induced NOR1 expression during neointimal SMC proliferation.…”
Section: Discussionmentioning
confidence: 96%
“…Klemm et al 33 reported a negative correlation between the expression level of CREB and proliferation of VSMCs. Platelet-derived growth factor decreased the CREB content in VSMCs and increased proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a role for p38 MAPK-dependent CREB-1 phosphorylation in the induction of growth was further confirmed by the inability of its dominant negative mutant to suppress either PDGF-BB-or thrombin-induced DNA synthesis in VSMC. It was recently reported that CREB plays an important role in VSMC differentiation-specific gene regulation (44). This study further showed that CREB is a negative regulator of VSMC growth.…”
Section: Discussionmentioning
confidence: 48%